1996
DOI: 10.1021/jo952199h
|View full text |Cite
|
Sign up to set email alerts
|

The C4H5+ Potential Energy Surface. Structure, Relative Energies, and Enthalpies of Formation of Isomers of C4H5+

Abstract: The potential energy surface for C4H5 + as calculated by ab initio molecular orbital theory is reported at two levels of theory, HF/6-31G(d,p) and MP2(full)/6-311G(d,p). Fourteen minima have been located at HF/6-31G(d,p), but inclusion of electron correlation reduced this number to nine. The methylcyclopropenyl cation, 1, is the global minimum, and the 2-cyclobutenyl (2), α-vinylvinyl (3), γ-methylpropargyl (4), α-methylpropargyl (5), and 1-cyclobutenyl (6) cations are 9.1, 19.9, 25.3, 27.5, and 26.9 kcal/mol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 65 publications
(36 reference statements)
4
31
0
Order By: Relevance
“…However, both cis ‐ and trans ‐ form of buta‐1,3‐dien‐4‐yl cation cannot be located at ω B97X‐D/6‐31+g(d,p) level. In a previous C 4 H 5 + PES study, Hopkinson and co‐workers found that trans ‐buta‐1,3‐dien‐4‐yl cation could be located only at HF level, but not at MP2 or MP4 level, and it can collapse into buta‐1,2‐dien‐4‐yl cation (CH 2 CHCCH 2 + ) via low barrier. Previous investigations about photodissociation of 1,3‐butadiene have also suggested that formation of buta‐1,2‐dien‐4‐yl is more favorable among the two possible channels to produce C 4 H 5 + from C 4 H 6 + .…”
Section: Resultsmentioning
confidence: 99%
“…However, both cis ‐ and trans ‐ form of buta‐1,3‐dien‐4‐yl cation cannot be located at ω B97X‐D/6‐31+g(d,p) level. In a previous C 4 H 5 + PES study, Hopkinson and co‐workers found that trans ‐buta‐1,3‐dien‐4‐yl cation could be located only at HF level, but not at MP2 or MP4 level, and it can collapse into buta‐1,2‐dien‐4‐yl cation (CH 2 CHCCH 2 + ) via low barrier. Previous investigations about photodissociation of 1,3‐butadiene have also suggested that formation of buta‐1,2‐dien‐4‐yl is more favorable among the two possible channels to produce C 4 H 5 + from C 4 H 6 + .…”
Section: Resultsmentioning
confidence: 99%
“…A number of minima and several transition structures permitting interconversion between the minima have been located on the potential energy surface. The methylcyclopropenyl cation is the global minimum (Cunje et al, 1996), and five other isomers are above the global minimum by 9.1 to 26.9 kcal/mol. Because of the existence of multiple minima on the potential energy landscape and substantial barriers to the isomerization processes, each isomer is trapped at the bottom of its corresponding minimum well without the possibility to convert to the lowest energy geometry.…”
Section: Future Studies and Concluding Remarksmentioning
confidence: 98%
“…The biggest hurdle (Ricks et al, 2010;Garand et al, 2008) in infrared and microwave spectroscopy experiments is to selectively study a sufficiently cold isomer of a molecular ion in an isolated condition, even if it is well demonstrated that rotational spectrometers based on jet expansion and Fourier Transform technique are able to characterize different conformers at the same time (Cocinero et al, 2012;Pena et al, 2012). As an example, the C 4 H 5 + potential energy surface (Cunje et al, 1996), as evaluated by ab initio computations, is highly complex. A number of minima and several transition structures permitting interconversion between the minima have been located on the potential energy surface.…”
Section: Future Studies and Concluding Remarksmentioning
confidence: 99%
“…The internally highly excited product ions further stabilize by the formation and elimination of molecular hydrogen. 116 In a third step, a hydrogen atom might be ejected from the C 4 H 3 +…”
Section: Cation-radical Reactionsmentioning
confidence: 99%